Senior housing policy in Poland: Determinants and desiderata - Lidia Groeger (European Spatial Research and Policy)
This paper aims to determine the comprehensive actions (which require interdisciplinary cooperation) to optimally prepare a high-quality housing environment for the growing population of seniors in Poland in the context of the current housing situation and the need to foster sustainable development. The paper outlines the determinants and specific actions to be taken to implement an effective senior housing policy in Poland. The study is based on the analysis of data obtained from the CSO on the senior housing environment, publications which study the expectations of the growing senior population and on the author’s own research conducted in 2024 among seniors residing in urban and rural areas. The results are a set of recommendations to facilitate the implementation of a rational housing policy targeted at the needs of seniors.